2012
DOI: 10.1111/j.1708-8305.2012.00626.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute Febrile Respiratory Reaction After Praziquantel Treatment During Asymptomatic Late Form of Acute Schistosomiasis: Table 1

Abstract: Paradoxical reactions (Jarish Herxheimer-like reactions) have been described in patients treated with praziquantel (PZQ) during acute schistosomiasis (infected≤ 3 mo), while PZQ treatment of chronic schistosomiasis is generally considered to be safe. We report an acute febrile reaction with respiratory decompensation following PZQ treatment in a 17-year-old male patient who had no potential (re)exposure to infection for at least 5 months and was therefore considered to have reached the chronic stage of disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The present study reported different proportions of AEs comparable to those found in other studies involving praziquantel and / or albendazole. However, there are variations that may occur due to the heterogeneous antecedents of the participating individuals, such as age, nutritional and immunological status, socioeconomic conditions, environmental exposure, prevalence and intensity of infection, stage of parasite development, etc [13,18,20,21,[31][32][33][34][35][36][37]. Zwang et al reviewed the efficacy and safety of PZQ (40mg/kg), and report that the main AEs experienced and their incidences are mainly abdominal pain (31.8%), muscle pain (29.2%), joint pain (20.2%), headache (13.6%), diarrhoea (12.9%), fatigue (9.6%), nausea (10.6%), dizziness (11.9%), vomiting (7.9%) and itching (9.8%) [18].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The present study reported different proportions of AEs comparable to those found in other studies involving praziquantel and / or albendazole. However, there are variations that may occur due to the heterogeneous antecedents of the participating individuals, such as age, nutritional and immunological status, socioeconomic conditions, environmental exposure, prevalence and intensity of infection, stage of parasite development, etc [13,18,20,21,[31][32][33][34][35][36][37]. Zwang et al reviewed the efficacy and safety of PZQ (40mg/kg), and report that the main AEs experienced and their incidences are mainly abdominal pain (31.8%), muscle pain (29.2%), joint pain (20.2%), headache (13.6%), diarrhoea (12.9%), fatigue (9.6%), nausea (10.6%), dizziness (11.9%), vomiting (7.9%) and itching (9.8%) [18].…”
Section: Discussionmentioning
confidence: 99%
“…Zwang et al reviewed the efficacy and safety of PZQ (40mg/kg), and report that the main AEs experienced and their incidences are mainly abdominal pain (31.8%), muscle pain (29.2%), joint pain (20.2%), headache (13.6%), diarrhoea (12.9%), fatigue (9.6%), nausea (10.6%), dizziness (11.9%), vomiting (7.9%) and itching (9.8%) [18]. Additionally for ALB, there are reports of the occurrence of epigastric pain, dry mouth, fever and itching [18,21,32,[38][39][40]. However, the occurrence of AEs are reported to be associated with the proportion of dying S. haematobium worms, i.e., with the pharmacologic effect of the drug on the parasite (for example; abdominal pain is reported to be associated with the deposition of dead worms in the mesenteric veins), they can also occur due to the natural course of disease [19,32,37,41,42].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When used to treat acute schistosomiasis, praziquantel can precipitate a paradoxical worsening, including urticaria, bronchospasm, or encephalopathy, which may require adjunctive corticosteroids for severe complications. [16][17][18][19] Post-exposure prophylaxis with praziquantel did not prevent acute or chronic schistosomiasis when given early (2 weeks after exposure) but when given later (4-6 weeks after exposure), prevented acute but not chronic schistosomiasis. 17 Some recommendations suggest that treatment should be deferred until 12 weeks after last exposure, and repeated 2-4 weeks later if infection persists.…”
Section: Treatmentmentioning
confidence: 86%